Building mobile mashup applications : some challenges encountered in computer science degrees - Díaz, Francisco Javier
The utilization and development of innovative technologies are suitable elements to take into account in Computer Science degrees. Modern technologies must be incorporated to portray the fundamental concepts and, in this way, to familiarize students with their future workplaces. The development of mashups for mobile devices turns out to be an appealing topic of great interest for students that attend technology and computer science courses. It represents a challenge when it comes to develop software for platforms with peculiarities such as screen and hardware restrictions, and with new advantageous features like sensors of movement, GPS and camera. In this article, it is described the experience in the development of mobile mashups applications written in JAVA in its two platforms: JME and Android. This work is the result of an articulation between a research project on a mobile application testbed and a Computer Science School subject in which the students obtain new skills in the development of software.